2003
DOI: 10.1016/j.ehj.2003.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic periodontitis, a significant relationship with acute myocardial infarction

Abstract: Our findings suggest that patients who at routine dental visits demonstrate evidence of bone loss around several teeth can predictably be identified as being at risk for future AMI. Such subjects should be referred for medical and periodontal examinations and treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 39 publications
8
62
1
Order By: Relevance
“…After their exclusion, 38 articles were selected for further full-text review. Eventually, 17 studies (Emingil et al, 2000; Rutger Persson et al, 2003; Deliargyris et al, 2004; Renvert et al, 2004; Cueto et al, 2005; Andriankaja et al, 2006, 2007; Kaisare et al, 2007; Stein et al, 2009; Willershausen et al, 2009, 2014; Holmlund et al, 2011; Kodovazenitis et al, 2011, 2014; Khosravi Samani et al, 2013; Wożakowska-Kapłon et al, 2013; Rydén et al, 2016) were included in our meta-analysis. A flow diagram of search process and results is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After their exclusion, 38 articles were selected for further full-text review. Eventually, 17 studies (Emingil et al, 2000; Rutger Persson et al, 2003; Deliargyris et al, 2004; Renvert et al, 2004; Cueto et al, 2005; Andriankaja et al, 2006, 2007; Kaisare et al, 2007; Stein et al, 2009; Willershausen et al, 2009, 2014; Holmlund et al, 2011; Kodovazenitis et al, 2011, 2014; Khosravi Samani et al, 2013; Wożakowska-Kapłon et al, 2013; Rydén et al, 2016) were included in our meta-analysis. A flow diagram of search process and results is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were conducted in European countries (Emingil et al, 2000; Rutger Persson et al, 2003; Deliargyris et al, 2004; Renvert et al, 2004; Cueto et al, 2005; Stein et al, 2009; Willershausen et al, 2009, 2014; Holmlund et al, 2011; Kodovazenitis et al, 2011, 2014; Wożakowska-Kapłon et al, 2013; Rydén et al, 2016), 2 studies were conducted in USA (Andriankaja et al, 2006, 2007) and 2 were conducted in Asian countries (Kaisare et al, 2007; Khosravi Samani et al, 2013). Within the included studies, a total of 3456 MI patients and 3875 non-MI control subjects had been evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, various studies conducted on different populations have suggested that atherosclerosis and the occurrence of AMI could be linked to periodontal infections (Arbes, Slade & Beck, 1999;Buhlin et al, 2002;Persson, Ohlsson, Pettersson, & Renvert, 2003;Smeets et al, 2001;Stein et al, 2011) However, on the other hand, several recent studies and meta-analyses have failed to identify any association between these two conditions Bokhari, 2006;Bokhari, Khan, Azhar, & Shahbaz, 2009;Humphrey, Fu, Buckley, Freeman & Helfand, 2008;Joshipura et al, 2011;Malthaner et al, 2002;Renvert, Ohlsson, Pettersson & Persson, 2010;Tuominen et al, 2003). After accounting for factors common to both periodontal disease and cardiovascular diseases, these studies found no significant association between periodontal disease and cardiovascular diseases, including AMI.…”
Section: Infection-induced Perturbations In Lipid Profiles As Per Thmentioning
confidence: 99%